2006
DOI: 10.1210/en.2006-0075
|View full text |Cite
|
Sign up to set email alerts
|

Novel Early Target Genes of Parathyroid Hormone-Related Peptide in Chondrocytes

Abstract: We have performed microarray analysis to identify PTHrP target genes in chondrocytes. ATDC5 cells were cultured as micromasses to induce chondrocyte differentiation. On d 8 of culture, the cells had a prehypertrophic appearance. This time point was chosen for isolation of RNA at 0, 1, 2, and 4 h after a challenge with 10(-7) M PTHrP. Samples were subjected to a cDNA microarray using competition hybridization. A list of 12 genes (P < 10(-3)), the expression regulation of which by PTHrP was confirmed by quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 90 publications
1
25
0
Order By: Relevance
“…In addition, during this process cells become responsive to PTHrP and in agreement with in vivo studies PTHrP inhibits hypertrophic chondrocyte differentiation [16, 17]. Previously, we have identified novel early response genes of PTHrP [18]. In this study, we focus on the identification of late PTHrP response genes regulated 24 or 72 h after PTHrP treatment.…”
Section: Introductionsupporting
confidence: 63%
See 4 more Smart Citations
“…In addition, during this process cells become responsive to PTHrP and in agreement with in vivo studies PTHrP inhibits hypertrophic chondrocyte differentiation [16, 17]. Previously, we have identified novel early response genes of PTHrP [18]. In this study, we focus on the identification of late PTHrP response genes regulated 24 or 72 h after PTHrP treatment.…”
Section: Introductionsupporting
confidence: 63%
“…Previously, we have shown that the cells have a pre-hypertrophic phenotype at this stage of culture [18]. PTHrP treatment at day 8 resulted in inhibition of the outgrowth of cartilage matrix 72 h later (fig.…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations